Prediction of earthquake by machine learning models and neural network - Xu Bohong (ITM Web of Conferences)
The occurrence of earthquakes has been examined from many aspects. Obviously, earthquakes occur without any warning and can damage entire cities in just a moment, causing enormous casualties and large amount of economic loss. In the last few years, people have given great effort to examine the earthquake from many aspects with various methods. The use of machine learning has solved seemingly intractable problems, inspiring the prospect of finding suitable solutions to dilemmas that are now considered unsolvable. Earthquake prediction, in this article, is executed with a neural network and machine learning models. After reading many articles, the author discovered that not many articles use a fully connected neural network to predict earthquake magnitude. In this article, the author first process the dataset sought from the internet, then predict the magnitude and the alert of earthquakes, with four machine learning models and a neural network. After that, the result of the accuracy are shown at the end of the article.